PENGARUH STRATEGI KOMUNIKASI PEMASARAN AISY DRINK MELALUI MEDIA SOSIAL TERHADAP MINAT BELI KONSUMEN DI KOTA BIMA (Universitas Muhammadiyah Palembang, 2022)
Satisfying consumer need is the desire of every company. Apart from being an important factor for the survival of the company, satisfying consumer needs can increase its superiority in the competition. Consumers who are satisfied with products and services tend to repurchase the product and reuse the service when the same need reappears in the future. This study aims to determine the effect to aisy drink marketing communication strategy on consumer buying interest in the city of Bima. This study uses a quantitative approach with a survey method. The population in this study are consumers who have seen marketing communication strategies through prmotions, the number of samples taken in this study were 50 respondents with the sampling used in this study was purposive sampling. The research instrument used a questionnaire with a likert scale. Data analysis used simple linear regression, partial test with t test. To test the effect between variables using SPSS (Statistical service product solutions) version 20.00. The results showed that the marketing communication strategy of aisy drink through social media had a positive effect on buying interest at AISY in Bima city.